ВПЛИВ ХІМІЧНИХ І ФІЗИЧНИХ МЕТОДІВ НА ФЛОТАЦІЙНЕ РОЗДІЛЕННЯ ПОРОШКІВ СИНТЕТИЧНОГО АЛМАЗУ ЗА МІЦНІСТЮ - Олійник, Нонна; Базалій, Галина; Ільницька, Галина; Заболотний, Сергій (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2025)
The work is devoted to the establishment and comparative analysis of the index of strength under static compression and homogeneity in terms of strength of the original grinding powder, grinding powder after preliminary chemical treatment and products of flotation separation of these powders. Attention is paid to powders of the AС20 grades with a grain size of 100/80. The research was carried out with the help of methods developed at the Institute of Informatics named after V.M. Bakul. It was established that the application of powder surface preparation due to the use of chemical and physical methods of special preparation and flotation separation changes the composition of the synthetic diamond powder, which is reflected in the differential and integral distribution of the grinding powder according to the strength index under static compression. There is an increase in the maximum distribution of the powder in the range of 3.6-21 N (up to 83% in the foam product compared to the original powder (70%), or the chamber product (71%)). The use of flotation separation allows you to obtain synthetic diamond powders with a changed composition of the original grinding powder and grinding powder after chemical cleaning and powders, and powders that can be obtained as a result of flotation separation. It is possible to obtain powders from foam products with significantly improved strength uniformity indicators at the level of 20-30%, compared to the original powder (16-18%) and strength uniformity indicators of chamber products (12-15%)). With the chamber products, it is possible to obtain powders with reduced indicators of homogeneity in terms of strength (12-15%)) (compared to the original powder (16-18%). The strength index of such powders under static compression is 13.0-12.3 N. The obtained results of the approximation of the integral distribution curves by the strength index during static grain compression indicate increased uniformity in the strength index of powders from foam products and reduced uniformity of powders from chamber products with a reliability of 0.87-0.98.   Key words: synthetic diamond grinding powder, flotation separation, strength index under static compression, uniformity of powder strength